Effects of Resveratrol and Potassium Bromate on Cholesterol, Vitamin E and A Level in Lung, Liver and Kidney of Wistar Rats - Keser, Serhat; Yilmaz, Okkes; Tuzcu, Mehmet (Gazi Univ, 2012)
In the present study, Wistar rats were randomly divided into three groups: 1. Control (C), 2. KBrO3 (K), 3. Resveratrol+KBrO3 (R). In tissues, cholesterol and vitamins analyses were performed by HPLC. According to our results, while the level of cholesterol increased in the K group, its level decreased in the R group when compared to C group in the lung. d-tocopherol and cholesterol levels decreased in the K and R groups when compared to C group in the liver. Retinol and cholesterol levels decreased in the K and R groups when compared to C group in the kidney. In conclusion, our results indicated that the applications of resveratrol and potassium bromate influenced cholesterol and lipophylic vitamins levels and these applications can be affected cholesterol biosynthesis in Wistar albino rats.
Keywords: Resveratrol; potassium bromate; liver; kidney; cholesterol